(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2016)
Lecture given at the Conference Le forme del testo. Editoria e filologia in Italia tra Otto e Novecento, University of Florence, 17-18 may 2016. The quarrel between the text that an author would like to give to his readers and the actually published text involves two other themes: “last author’s wills” and «approximation to value» that leads to the first or to the following editions. Author’s idea of his work, in fact, evolves in time, before and after the publication, and it is necessary to distinguish whether editors intrusion has been ‘licensed’ by authors or not.